2013
DOI: 10.1159/000356347
|View full text |Cite
|
Sign up to set email alerts
|

Circle of Willis Configuration as a Determinant of Intracranial Dolichoectasia

Abstract: Background: Circle of Willis (COW) variants might influence arterial caliber in the brain. We hypothesized that these variants would be associated with the prevalence of intracranial dolichoectasia (DE). Methods: We examined COW variants and DE in a sample of stroke-free participants (n = 436) undergoing magnetic resonance angiography (MRA) as part of a population-based study. Large intracranial arterial diameters were obtained when available; if not, the artery was defined as hypoplastic or absent according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 60 publications
3
38
0
1
Order By: Relevance
“…This hypothesis is supported by the fact that in the presence of a fetal PCA the anterior circulation dominates the hippocampal blood flow and function (Hendrikse, van Raamt, van der Graaf, Mali, & van der Grond, 2005) and in the reciprocal relationship between left PCA with left Pcomm. (Gutierrez et al, 2013)…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by the fact that in the presence of a fetal PCA the anterior circulation dominates the hippocampal blood flow and function (Hendrikse, van Raamt, van der Graaf, Mali, & van der Grond, 2005) and in the reciprocal relationship between left PCA with left Pcomm. (Gutierrez et al, 2013)…”
Section: Introductionmentioning
confidence: 99%
“…While the study showed that BA diameter was associated with an increased risk of adverse vascular outcomes, that evaluation was done only in participants with non-fetal types CoW, and the relevance of having lower BA diameter related to fetal type CoW was not assessed. Likewise, in the Northern Manhattan Study, smaller BA diameters were noticed in individuals with fetal type CoW, but as the authors correctly noticed, the relevance of this finding is still unknown [3]. …”
Section: Discussionmentioning
confidence: 99%
“…In this view, it is possible that a BA that is not required to provide blood supply to territories irrigated by one or both posterior cerebral arteries – as it occurs in the fetal type Circle of Willis (CoW) – is not submitted to flow-induced outward vascular remodeling, and hence has a smaller diameter. However, the influence of CoW variants in BA diameter has been evaluated only in 2 studies [3, 4], and more information is needed to confirm these findings. In this study, we aimed to assess whether BA diameter associates with the presence of fetal type CoW in community-dwelling older adults living in rural Ecuador.…”
Section: Introductionmentioning
confidence: 99%
“…First, it does not take into account that the contralateral homonymous arterial diameter is affected by the collateral flow on that side, that is, if there is a large anterior cerebral artery branching off from the same internal carotid artery, the middle cerebral artery would be expected to be smaller. 2 Second, it does not take into account the normal arterial taper in size as the artery extends further into the skull, and thus the use of the proximal arterial segment as a referent may falsely lead to an overestimation of positive remodeling. Using the distal poststenotic segment is also problematic as poststenotic dilatation may occur.…”
Section: To the Editormentioning
confidence: 99%